Estimating the population size of men who have sex with men: a modified Laska, Meisner and Siegel procedure taking into account internet populations. Issue 2 (1st September 2012) - Chen, Hao; Zhang, Yanhui; Tan, Hongzhuan; Lin, Dan; Chen, Mengshi; Chen, Niannian; Bao, Yugang; Wen, Shiwu
Abstract : Objectives: Men who have sex with men (MSM) are an at-risk population for HIV/AIDS. Accurately estimating the size of MSM is important to monitor the HIV/AIDS epidemic and to implement HIV/AIDS prevention in the MSM population. None of the current methods for MSM population size estimation is satisfactory, especially for internet samples. We try to use the modified Laska, Meisner and Siegel (LMS) method to estimate the size of MSM in tangible venues and internet virtual venues. Methods: Laska, Meisner and Siegel developed an unbiased estimator for the size of a population in a single venue based on a single sample (LMS method). In this study, we modified the LMS method for the estimation of population size of MSM (LMS* procedure). Specially, we integrated the MSM size of traditional tangible venue with internet virtual venue. Currently, the latter is an important source of socialisation for MSM population. To do this, we added a few parameters to the original LMS method. Then we applied the LMS* procedure to estimate the size of MSM in Changsha, the capital city of the Chinese Province of Hunan. Results: The LMS* procedure handled the complexity of socialisation among MSM population well. According to the LMS* procedure, the total number of MSM was 65 657 (95% CI 57 922 to 73 388), constituting a proportion of 5.43% (95% CI 4.79% to 6.07%) in the sexually active male population (15–64-year-olds) in Changsha. Conclusions: We conclude that the LMS* procedure is suitable for the estimation of a hard-to-reach population, such as MSM, in tangible venues and internet virtual venues.